Upaya Peningkatan Disiplin Peserta Didik - Mohamad Muspawi; Bradley Setiyadi; Fitriana Fitriana (Universitas Batanghari Jambi, 2022)
This study aims to describe the principal's leadership in improving student discipline at SMKN 2 Tanjung Jabung Timur Jambi as well as the supporting and inhibiting factors. Using a qualitative approach with the type of case study research. The subjects are principals, teachers and students. Using observation, interviews and documentation studies for data collection techniques. The data analysis technique uses data reduction, data presentation and conclusion drawing. While the data validity test uses data triangulation. The results show that (1) the efforts made by the principal to improve student discipline are by a. self concept, b. communication skills, c. logical and natural consequences, and d. integrity discipline. (2) The inhibiting factors are a. Many students are not willing to apply disciplinary rules, b. lack of exemplary, c. social environment, d. family and parents of students, e. as well as differences in habits from the previous school.